Husnuzzhan terhadap Efikasi Diri pada Mahasiswa UIN Antasari dalam Menyusun Skripsi - Pratiwi, Desita Kosalia; Abidin, Muhammad Zainal; Fadhila, Mahdia (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This research is a field research with quantitative research methods. Aims to determine the effect of husnuzzhan on the self-efficacy of UIN Antasari Banjarmasin students in compiling Thesis. The population in this study were active students of UIN Antasari Banjarmasin class of 2016, totaling 651 students. The sampling technique used was purposive sampling, with a total sample of 227 people. Based on the research conducted, the results obtained: 1) The level of self-efficacy in the high category was 62 people (27%), in the medium category as many as 163 people (70.9%), and in the low category as many as 2 people (0,9%). 2) The level of husnuzzhan in the high category was 164 people (71,3%), in the medium category as many as 63 people (27,4%), there were no students ib the low category. 3) Husnuzzhan's contribution to the self-efficacy of UIN Antasari Banjarmasin students in the preparation of Thesis with a significance value of 0.000 (P < 0.005) and an effective contribution of 47.2%. Ha is accepted and there is a positive relationship, namely: the higher the husnuzzhan, the higher the self-efficacy, and vice versa.